Customer Satisfaction on Internet Service Providers in Albania - Buhaljoti, Ana (European Scientific Journal, ESJ, 2019)
The internet access in Albania has been growing steadily over the past decade, enhancing competitiveness and sustaining economic growth. Internet service providers (ISPs) have been raising significantly and competition is increasing. Thus, it is relevant to understand why customers stay with a particular service provider. The study sought to investigate the factors influencing customer satisfaction towards Internet Service Providers in Albania. Primary data were collected from 430 subscribers of ISPs by using a face to face survey methodology. The SERVPERF model was employed to identify the factors influencing internet services access. Results show that customer satisfaction is highly influenced by the Quality of the Service as the most important determinant of perceived service value which can enhance satisfaction in customer’s opinion. The study implicates the marketing professionals in the telecommunications industry who are responsible for designing marketing strategies to foster competition and increase market share. The practical approach of the study involves an analysis of consumer perceptions in this market and strategic recommendations for ISPs.